SPE/IADC Drilling Conference and Exhibition 2011
DOI: 10.2118/140011-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Experimental Backward Whirl Simulations for Rotary Steerable Bottom Hole Assemblies

Abstract: A unique analytical model has been developed to predict dynamic behaviour of the drilling assembly and gain a better understanding of the dominant factors that cause backward whirl. A full-scale test rig has been constructed that is capable of initiating and sustaining full rolling contact backward whirl, repeatably, reliably and safely. Excellent correlation between these near real time analytical simulations and full-scale experimental results has been achieved giving confidence in using the model for seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…2, where X is the axial direction (along the direction of the drillstring) and Y and Z are in the lateral directions. The radial and tangential directions are similar to Y and Z, but offset and rotated about the tool center line (Brazil et al 2002;Sugiura 2005).…”
Section: Downhole-data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…2, where X is the axial direction (along the direction of the drillstring) and Y and Z are in the lateral directions. The radial and tangential directions are similar to Y and Z, but offset and rotated about the tool center line (Brazil et al 2002;Sugiura 2005).…”
Section: Downhole-data Acquisitionmentioning
confidence: 99%
“…For example, the theoretical frequency for backward whirl is given by (Vandiver et al 1990;Stroud et al 2011):…”
Section: Appendix A: Theoretical Equations For Bending Caused By Whirlmentioning
confidence: 99%
See 1 more Smart Citation
“…2, where X is the axial direction (along the direction of the drillstring) and Y and Z are in the lateral directions. The radial and tangential directions are similar to Y and Z, but offset and rotated about the tool center line (Brazil et al 2002;Sugiura 2005). In addition to the high-frequency data, statistics and averages of the measurements are also recorded to low-frequency memory at 0.5Hz.…”
Section: Downhole Data Acquisitionmentioning
confidence: 99%
“…Other researchers have used two sets of accelerometers in a rotary steerable system (RSS) to detect and quantify collar/stabilizer whirl (Minett-Smith et al 2010). Using the same sensor, Stroud et al (2011) showed the motion of the collar in transition from "rolling-sliding" to "backward whirl" in laboratory testing.…”
Section: Introductionmentioning
confidence: 99%